ANTIBACTERIAL ACTIVITY OF ELEVEN SOUTH AFRICAN PLANTS USE IN TREATMENT OF DIARRHOEA IN FOLKLORIC MEDICINE - Kaikabo, Adamu Ahmad; Suleiman, M. M.; Samuel, Babatunde B.; Eloff, J. N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Antibacterial activity of eleven South African plants use in treatment of diarrhoea in folkloric medicine were examined The acetone extracts of eleven South African plants belonging to nine families, were screened for their antibacterial properties by determination of their minimum inhibitory concentrations (MIC) against 4 nosocomial bacterial pathogens. MIC screening was conducted at concentrations of 0.02 to 2.5 mg/ml using a two-fold serial microdilution method1 against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli and Pseudomonas aeruginosa. All the extracts had activity against at least one of the test organisms over a period of 1, 2 or 24 hours. The extracts of Macaranga capensis, Garcinia livingstonei, Diospyros rotundifolia and Dichrostachys cinerea had good antibacterial activity with minimum MIC values of 0.03, 0.04, 0.06 and 0.08 mg/ml, respectively. The average MIC values of the plant extracts against the tested pathogens ranged from 0.23-1.77 mg/ml. S. aureus was the most susceptible bacterial pathogen with average MIC of 0.36, the extract of Diospyros rotundifolia was the most active with activity against all the organisms and had a lowest average MIC of 0.23 mg/ml when compared with other extracts. The extracts of Buxus natalensis, Dracaena mannii, and Pittosporum viridiflorum, Acacia sibeiriana, Erythrina lattissima, Cassine papillosa and Pavetta schumanniana had low antibacterial activity at the concentrations used.References: 1. Eloff JN, 1988 Planta Medica 64, 711-714.